Bladder endometriosis-A great masquerader (Indian Journal of Case Reports, 2024)
The bladder is the most common site affected in urinary tract endometriosis. There is a controversy regarding the pathogenesis, clinical management (diagnosis and treatment), impact on fertility, and the risk of malignant transformation of bladder endometriosis. Patients presenting with symptoms typically attributed to endometriosis might go unnoticed because of its infrequent occurrence. We, hereby, report a case of a young female who had complaints of burning micturition and dysmenorrhea. After a thorough evaluation, she was found to have a urinary bladder mass which was subjected to a biopsy. The initial histopathology report came as bladder malignancy but immunohistochemistry proved otherwise and it turned out to be urinary bladder endometriosis.